Aesthetic practice in covid times-evolving guidelines at the cosmetic clinic - Kuldeep Singh; Shahin Nooreyezdan; Pankaj Mehta; Amrit Shankar Shastry; Gaurav Kumar; Kriti Agarwal; Uma Krishna; Pulkit Arora (Apollo Medicine, 2020)
Background: The coronavirus disease 19 (COVID-19) pandemic has led to an almost complete initial halt of all elective surgical and medical procedures, more so in the practice of esthetic surgery and medicine, globally. As practices are trying to open up, the when, how, and what services can be scheduled again are the questions which arise in front of all service providers. Stringent infection control measures are the need of the hour in response to the current continuing COVID-19 pandemic. In esthetic clinics, guidelines for infection control measures as well as protocols for performing procedures are of particular importance for their safe and smooth functioning. Methods: A Medline/PubMed search was conducted for any and all possible publications on esthetic guidelines for safe functioning during the COVID pandemic. Advisories by the governments of the day, the World Health Organization, as well as those issued by various national and international esthetic societies were also taken into consideration. A set of protocols and preferred practice guidelines were drafted to allow functioning of the esthetic clinics as well as protect the doctors, clinic staff, and patients from the SARS-CoV-2 infection. Results: “Standard operating procedure (SOP)” guidelines for esthetic clinics were drafted and put into place in our Aesthetic Clinic at Indraprastha Apollo Hospital after going through all possible recommendations for scheduling patients, screening at entry, declaration and esthetic consultations, and for safety precautions about the different procedures and later categorized into low risk, moderate risk, and high risk based on the possibility of the transmission of SARS-CoV-2 virus from a possible infected patient to the treating physician or therapist, and the other way around. Conclusions: The SOP provides sound infection control measures for esthetic practices. There are guidelines regarding safety measures and use of personal protective equipment during scheduling, distancing, and risk-wise categorization, and also what procedures are permitted. These may vary from country to country, but local and national guidelines should be incorporated and followed to prevent the COVID-19 infection in esthetic clinics.